Biosurfactants in Plant Protection Against Diseases: Rhamnolipids and Lipopeptides Case Study - Crouzet, Jérôme; Arguelles-Arias, Anthony; Dhondt-Cordelier, Sandrine; Cordelier, Sylvain; Pršić, Jelena; Hoff, Gregory; Mazeyrat-Gourbeyre, Florence; Baillieul, Fabienne; Clément, Christophe; Ongena, Marc; Dorey, Stéphan (Frontiers in Bioengineering and Biotechnology, 2020)
Biosurfactants are amphiphilic surface-active molecules that are produced by a variety of microorganisms including fungi and bacteria. Pseudomonas, Burkholderia, and Bacillus species are known to secrete rhamnolipids and lipopeptides that are used in a wide range of industrial applications. Recently, these compounds have been studied in a context of plant-microbe interactions. This mini-review describes the direct antimicrobial activities of these compounds against plant pathogens. We also provide the current knowledge on how rhamnolipids and lipopeptides stimulate the plant immune system leading to plant resistance to phytopathogens. Given their low toxicity, high biodegradability and ecological acceptance, we discuss the possible role of these biosurfactants as alternative strategies to reduce or even replace pesticide use in agriculture.